Occurrence of Polycyclic Aromatic Hydrocarbons (PAHs) in Pyrochar and Hydrochar during Thermal and Hydrothermal Processes - Hwang-Ju Jeon; Donghyeon Kim; Fabiano B. Scheufele; Kyoung S. Ro; Judy A. Libra; Nader Marzban; Huan Chen; Caroline Ribeiro; Changyoon Jeong (Agronomy)
Pyrochar (Biochar) produced from the thermochemical conversion of biomass has been widely used as a soil amendment to improve agricultural soil quality. Since polycyclic aromatic hydrocarbons (PAHs) can be produced in such processes, the occurrence of PAHs in pyrochars has been extensively studied, and standards such as the European Biochar Certificate (EBC) and International Biochar Initiative (IBI) contain limit values for biochars applied to soils. However, studies on PAH levels in hydrochars from hydrothermal processes, which can be an alternative to wet biomass are scarce. This study focuses on comparing the occurrence of 16 PAHs regulated by the US EPA in 22 char samples (including pyrochars from pyrolysis, hydrochars from hydrothermal carbonization, and, for the first time, hydrothermal humification) using an ultrasonic extraction method. Results showed that the sum of the 16 EPA PAHs in all samples was well below the requirements of the two standards, except for pyrochar produced at the farm scale. They ranged from 131 to 9358 µg·kg−1 in the seven pyrochars and from not detected to 333 µg·kg−1 for the fourteen hydrochars. Our findings indicate that hydrochar produced via hydrothermal methods exhibits much lower concentrations and is a safe option for soil amendment and environmental applications.